Meningkatkan Keterampilan Menulis Puisi Menggunakan Model Problem Based Learning Pada Siswa Kelas V Sekolah Dasar - Siska, Reka; Astuti, Astuti; Azwari, Muhammad Azhil; Adinata, Hasrudi (Peneliti.net, 2025)
The aim of this research is to improve poetry writing skills using the problem based learning (PBL) learning model for class V students at SD Negeri 204/VII Tanjung Raden III. The type of research is classroom action research (PTK). The research results show that learning to write poetry using the Problem Based Learning (PBL) learning model can improve poetry writing skills. This has been proven in student activities during the learning process in the initial pre-cycle conditions with an average score of only 53 and after taking action there was a gradual increase in cycle 1 with an average of 65 and cycle 2 with an average of 80. This happened because student activities support an intellectual attitude that is responsible individually and as a group.